Stillman's Drug Building - Pickford, Joel:::::::::
Rollin's photo of the Stillman Drug building by Fresno High School. The building was built by the artist's father, Rollin A. Pickford, Sr. in the 1940s. The main tenant, Stillman's Drug, boasted a soda fountain where Fresno High students sat at a counter and drank root beer floats. The Pickford family sold the building in 1977 to Navo Arax, uncle of author Mark Arax. The Arax family still owns it as of 2019.